Knowledge network for sustainable local development (2021)
This article aims to build a network for the exchange of knowledge between the government and production, community and university sectors for sustainable local development. To achieve this, the authors relied on the concepts of sustainable local development, social capital, the relationship between sectors or intersectorality, networks and interdisciplinary and transdisciplinary knowledge. Regarding the methodology, the abductive method was used. Under a documentary design, the research techniques were a content analysis of theoretical documents and the deductive inference technique. The construction of a knowledge exchange network for sustainable local development stands out as the result. It is concluded that knowledge networks for sustainable local development have positive implications in the establishment of alliances and links between the sectors that make up society.